Антиоксидантна активність скелетних м’язів гусей у передзабійному періоді - Данченко, Олена Олександрівна; Данченко, Елена Александровна; Danchenko, Olena; Здоровцева, Любов Миколаївна; Здоровцева, Любовь Николаевна; Zdorovtseva, Liubov; Данченко, Микола Миколайович; Данченко, Николай Николаевич; Danchenko, Mykola; Рубан, Г. В. (My University, 2018)
UK: Одним із напрямків підвищення ефективності гусівництва є науково обґрунтоване застосування біогенних домішок спрямованої дії, у тому числі антиоксидантних. З’ясовано особливості впливу показників прооксидантно- антиоксидантної рівноваги на антиоксидантну активність скелетних м’язів гусей у передзабійному періоді (з 35-ої до 63-ої доби). Зазначений проміжок онтогенезу гусей включає фізіологічну напругу в організмі птиці (з 42-ої до 56-ої доби), зумовлену формуванням ювенального пір’я. Перша половина досліду характеризувалася підвищенням вмісту ТБК-активних продуктів і зниженням коефіцієнта антиоксидантної активності на 41,8 %. Супероксиддисмутазна активність у часі мала тенденцію до зниження, а каталазна - до зростання. Упродовж досліду у скелетних м’язах достовірно зменшився вміст вітаміну А і в-каротину. Найбільш стабільним рівнем характеризувався вміст вітаміну Е (V =10,4 %). За допомогою кореляційного і кластерного аналізів з’ясовано вплив досліджених показників прооксида- нтно-антиоксидантної рівноваги скелетних м’язів гусей на їх антиоксидантну активність. За у < 0,10 досліджені показники утворюють три відокремлені кластери, а на рівні у < 0,24 встановлено наявність слабких тенденцій до кореляційних зв'язків між усіма дослідженими показниками, які об'єднують досліджені показники в єдину структуровану динамічну систему. Встановлено достатньо потужний прямий зв’язок між коефіцієнтом антиоксидантної активності і вмістом вітаміну Е у скелетних м’язах гусей, що свідчить про доцільність застосування підвищених концентрацій вітаміну Е в раціоні птиці у передзабійному періоді. RU: Одним из направлений повышения эффективности гусеводства является научно обоснованное применение биогенных добавок направленного действия, в том числе антиоксидантных. Определены особенности влияния показателей прооксидантно-антиоксидантного равновесия на антиоксидантную активность скелетных мышц гусей в предубойному периоде (с 35-ых по 63-ьи сутки). Указанный промежуток онтогенеза гусей включает физиологическое напряжение в организме птицы (с 42-ых по 56-ых сутки), обусловленное формированием ювенального оперения. Первая половина опыта характеризовалась повышением содержания ТБК-активных продуктов и снижением коэффициента антиоксидантной активности на 41,8 %. СОД-активность во времени имела тенденцию к снижению, а КАТ - к увеличению. С 35-ых по 63-ьи сутки достоверно уменьшилось содержание витамина А и Р-каротина. Наиболее стабильным уровнем характеризовалось содержание витамина Е (v = 10,4 %). Изучено влияние исследованных показателей прооксидантно-антиоксидантного равновесия скелетных мышц гусей на их антиоксидантную активность. На уровне статистической надежности у < 0,10 исследованные показатели образуют три кластера, а на уровне Y < 0,24 установлено наличие слабых тенденций к корреляционным связям между всеми исследованными показателями, которые объединяют исследованные показатели в структурированную единую динамическую систему. Установленная достаточно сильная прямая связь между антиоксидантной активностью и содержанием витамина Е в скелетных мышцах гусей свидетельствует о целесообразности применения повышенных концентраций витамина Е в рационе этой птицы в предубойном периоде. EN: Ukraine. The introduction of scientific achievements will improve the industry efficiency increasing. The food additives are added to the diet of the birds for increasing the antioxidant status in their organisms in the pre-slaughter period. However, it has been proved by the modern biochemical studies that even a little biogenic substance application can lead to the negative consequences. Thus, at this stage of the goose breeding development there is a need for scientifically based application of antioxidant additives. That’s why the goose functioning system research of the antioxidant protection peculiarities (AOP) during the pre-slaughter period can become a reliable scientific support for the biogenic antioxidant practical application in the goose breeding. The research aim is to find out the influence of the prooxidant-antioxidant balance on the antioxidant activity of skeletal muscles (SM) of geese in the pre-slaughter period. Studying the geese of Italian breed, from the 35th to the 63rd day, the research was conducted weekly. During this period, the geese of the experimental group had a balanced ration with exchange energy, proteins, vitamins and minerals in accordance with the recommendations for this age of geese. The lipid peroxidation intensity has been evaluated in accordance with the peroxidation product content in the gained biomaterial samples that react with 2-thiobarbituric acid. The determination of these substances has been carried out in the lipid extracts of SM and homogenates of these tissues initiated by the reaction of Fe2+ LPO. In addition, the quantity of general amount of lipids, vitamin E, vitamin A, P-carotene and the activity of antioxidant enzymes: superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPO) have been determined in the obtained biomaterial content. The state of the antioxidant protection system has been evaluated with the help of antioxidant activity index (AAI). The ontogenesis period of geese that has been mentioned is characterized by physiological stress in the body of the bird (from the 42nd to the 56th day) and it is caused by the juvenile feather formation. This process is accompanied by the LPO product content increasing in the SM of geese. AAI declines for 41.8% from the 42nd to the 56th day. Different activity changes have been researched for antioxidant enzymes: SOD-activity has the tendency to decrease over time, CAT-activity - to increase, and PPO-activity does not change significantly over time. The content of vitamin A and P-carotene has significantly decreased during the experiment. The content of vitamin E (v = 10,4%) is the most stable. A correlation and cluster analyses have been conducted for the determination of the integrated structure ordering characteristics of the researched indices of the prooxidant-antioxidant balance. These results have shown the antioxidant activity dependence of SM on the studied indices. The clustering of these indices on the basis of the correlation links between them at the significance level у < 0,10 has helped to discover three of these clusters: a basic cluster of six activity). GPO-activity remains in a separate form without any reliable connection correlation. However, taking into account the connection correlations and the statistical tendency level (y < 0,24), it is possible to study the presence of weak tendencies with the correlation relations between the indices that belong to the different clusters. These weak interactions combine all the researched indices in a single structured dynamic system. Thus, the prooxidant-antioxidant balance in the goose physiological state is done by the coherent functioning of all the studied indices. The researched strong connection between AAI and vitamin E content in the skeletal muscles of geese affirms the the vitamin E application in the bird diet during the pre-slaughter period.
Антиоксидантная активность скелетных мышц гусей в предубойном периоде
Antioxidant activity of goose skeletal muscles in the pre- slaughter period
Keywords: гуси; скелетні м’язи; прооксидантно-антиоксидантна рівновага; антиоксидантна активність; кореляційний аналіз; кластерний аналіз; гуси; скелетные мышцы; прооксидантно-антиоксидантное равновесие; антиоксидантная активность; корреляционный анализ; кластерный анализ; geese; skeletal muscles; prooxidant-antioxidant balance; antioxidant activity; correlation cluster; cluster analysis